2016
DOI: 10.2146/ajhp150135
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of barcode scanning by pharmacy technicians and pharmacists’ visual checks for final product verification

Abstract: The use of pharmacy technician barcode checking is a safe alternative to a pharmacist's visual check and, in appropriate cases, can allow reallocation of pharmacist time to clinically oriented patient care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 8 publications
0
18
0
1
Order By: Relevance
“…Six of the included studies utilised a pre and post-intervention methodology with prospective observations, [24][25][26][30][31][32] four were parallel arm prospective observational studies 22,[27][28][29] and one was a multi-phase prospective observational study. 23 The data collection periods ranged from 6 days to 1 year.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the included studies utilised a pre and post-intervention methodology with prospective observations, [24][25][26][30][31][32] four were parallel arm prospective observational studies 22,[27][28][29] and one was a multi-phase prospective observational study. 23 The data collection periods ranged from 6 days to 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…23 The data collection periods ranged from 6 days to 1 year. The majority of studies used a research pharmacist observer who identified dispensing errors independent to the dispensing process, 22,[24][25][26][27]30 while others incorporated the identification and documentation of dispensing errors into the final verification stage of the dispensing process. 23,24,29,31,32 In all but one study, those evaluating the presence of dispensing errors were not blinded to the study allocation of the medication orders or prescriptions being assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al demonstrated that implementing this technology during drug selection could significantly reduce error rates compared with mere visual checking (−0.07% error rate; P = .008). 7 An observational study conducted in a tertiary care facility, in which 14 041 medication administrations and 3082 order transcriptions were assessed, exhibited a 41.4% relative reduction in errors ( P < .001) after barcode scanning implementation. 8 In an additional study, a greater than 90% relative reduction in the incidence of pharmacy dispensing errors was observed when barcode scanning was employed ( P < .001).…”
Section: Introductionmentioning
confidence: 97%
“…De forma similar a la industria farmacéutica, cuando se trabaja en el sector hospitalario un error puede causar estragos en la vida de una persona, por lo que los sistemas de trazabilidad pueden ser encontrados en distintos sectores o procesos dentro de un hospital Wang et al (2016). implementan en un hospital un sistema de código de barras para apoyar con la medicación de los pacientes, con la finalidad de aumentar la seguridad de los pacientes y de reducir los errores del personal, esto debido a que son muchos paciente que cada doctor y enfermero atiende diariamente, lo que puede provocar confusión de las instrucciones para cada uno de ellos.…”
unclassified